La Cour provinciale et l'art. 96 de l'A.A.N.B. - Deslauriers, Jacques (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
In the Province of Quebec, the Provincial Court constitutes one of the most important benches after the Court of Appeal and the Superior Court. At its beginning in 1869, the Provincial Court was termed the Magistrate's Court and its juridiction was very circumscribed. The constitutional problem arising from the existence of such a court was not obvious as it is today. In 1867, when the B.N.A. Act was drafted, the powers concerning the administration of justice in the Province, including the constitution, maintenance and organisation of provincial courts, both civil and criminal, and including procedure in civil matters, were conferred on the provinces by section 92(14). But by section 96, it was provided that the Governor General should appoint the judges of the Superior, District and County courts in each province. These provisions of the B.N.A. Act are extremely confused, so that more than 130 published cases have not succeeded in clarifying definitively the interpretation of sections 96 and 92(14), and such a situation imperils the stability of the judiciary in the Canadian provinces. For the analysis of section 96 of the B.N.A. Act, we must refer to some concepts in English Law about Superior Courts and Inferior Courts. The Magistrate's Court, now the Provincial Court in Quebec, has in fact replaced the Circuit Court whose competence was exercised by judges of the Superior Court appointed by the Federal Government. It is not obvious that in 1867 the Circuit Court was an inferior bench in the mind of the drafters of the B.N.A. Act. At that time the inferior courts in the Province of Quebec were the Commissary Courts and the Justices of the Peace. In 1869 when the Magistrate's Court was established, nobody was wandering about the constitutional question because the jurisdiction of the Court was limited to the collection of municipal and school taxes and to suits actions in which the amount was less than $ 25.00. But in 1888 and 1889 when the Provincial Legislature attempted to replace the Circuit Court in the District of Montreal with the Magistrate's Court, the Federal Government disallowed the laws because judges appointed by the Provincial Government were invested with powers which were up to that time exercised by judges appointed by virtue of section 96 of the B.N.A. Act. The Federal Government was then invited to appoint judges especially affected to the Circuit Court of Montreal, but the Magistrate's Court continued to exist in other judicial districts without extent of jurisdiction. In 1922, the Provincial Legislature tried agin to raise the powers of the Magistrate's Court by transferring to it all the functions exercised by Superior Court judges in the Circuit Court. But at this moment, the Federal Government did not intervene with it's disallowance power. So, once the delay for disallowance had expired, the Provincial Government continued to raise the competence of the Magistrate's court until the abolition of the Circuit Court in 1952. Since 1952, the powers of the Magistrate's Court have not ceased to grow. In 1965, with the adoption of the new Code of Civil Procedure, the name of Magistrate's Court was changed to become the Provincial Court. In spite of it's importance, the constitutional question is not yet settled, and whatever method we use, we cannot justify the constitutionality of the Provincial Court. Several methods have been elaborated by judges to interpret section 96 of the B.N.A. Act. The particularist method consists in appreciating if a board or a bench is invested with powers which, in 1867, were exercised by judges appointed by the Federal Government. If so, the bench is considered inconstitutional. Another method is the functionalist method by which it is presumed that the judicial function should be exercised only by judges appointed by virtue of section 96. This method is not very often used. Finally, there is the globalist method which is more comprehensive but also more abstract, which consists in the recognition of the fact by the growth of its jurisdiction the Provincial Court has become a superior, district or county Court. Whatever method is used, it is very difficult to establish the constitutionality of the Provincial Court in the Province of Quebec. This situation incites a reflexion about the opportunity of section 96 of the B.N.A. ACT which restrains the Province from adopting judicial reforms that are very necessary. If after 110 years, we are not clear about the interpretation that should be given to section 96, we shall never be. In the actual context, the arguments presented by the Fathers of the Confederation for the drafting of section 96 are not very pertinent. If we examine other federal constitutions in foreign countries, it appears that in every case the drafters of such constitutions carefully avoid the situation in which we are placed by section 96 of the B.N. A. Act. Perhaps the better solution for us is the abrogation of section 96 of the B.N.A. act.